DEVELOPING LANGUAGE GAMES TO TEACH SPEAKING SKILL - Nurxonova Nafosat Husniddinovna; Tursunova Gulchexra Norboyevna (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
The effective teaching of speaking in a foreign language classroom presents persistent challenges, particularly among young learners. To counteract disengagement, limited interaction, and anxiety in language production, language games have emerged as dynamic tools that stimulate learner participation, enhance communicative competence, and foster motivation. This article explores the integration of games into speaking-focused English language teaching (ELT) by examining their classifications, pedagogical functions, and implementation strategies. It discusses the theoretical foundations of games as learning tools, outlines various types of games according to structure, language skills, and learner proficiency, and addresses potential challenges that may arise during their application. The study concludes that while games are not a panacea, when strategically employed, they offer a practical, learner-centered approach that facilitates speaking fluency, accuracy, and overall learner confidence.